The concentration of heavy metals and pollution indices in a selected abandoned mine in the State of Pahang, Malaysia - Mohd Zahari Abdullah; Fazrul Razman Sulaiman; Nur Sha’adah Zainuddin; Wan Noni Afida Ab Manan; Nazree Ahmad (Journal of Degraded and Mining Lands Management, 2023)
Abandoned iron ore mining soil was analyzed for its metal contamination. Pollution indices were calculated and used to examine the potential of the area to be polluted by the metals. The samples were collected in triplicate from ten sampling points spread throughout the mining area. The energy dispersive X-ray fluorescence (EDXRF) analytical method was used to determine the concentrations of Cd, Cu, Co, Pb, Zn, Fe, Cr, Ni, and Mn. The order of the mean metal concentrations (mg/kg) in soil samples taken at random from ten locations near the chosen iron ore mines is Fe, Mn, Cr, Pb, Cu, Zn, Co, Ni, and Cd. The Geoaccumulation Index (Igeo) results showed that the area was moderately contaminated, especially with Fe, whereas the results of the Enrichment Factor (EF) and the Quantification of Contamination (QoC) showed that metal enrichment was strongly related to anthropogenic origins. EF and Quantification of Contamination (QoC) results revealed that metal enrichment was strongly related to anthropogenic origins. The ecological risk based on individual metals followed the following order: Cd > Pb > Co > Cu > Cr > Fe > Ni > Mn > Zn, and the average Potential Ecological Risk Index (PERI) was recorded at the severely high-risk level. The findings clearly showed that the study area might pose a serious threat to environmental health.